Tanslation Method and Translation Technique on the Website of Indonesia.go.id - TUZHARA RAMADHANTY MAJID; Erwin Ashari; Shalehoddin Shalehoddin (English Education Department at FKIP Nommensen University, 2023)
Translation methods and translation techniques are needed to be able to translate a text well. The purpose of this study is to identify and analyze the types of translation methods and translation techniques available on the Indonesia.go.id website. To be able to conduct this research, a qualitative approach was used with a descriptive research design. The data in this study consisted of words, phrases, clauses, and sentences taken from the Indonesian and English versions of the text on the website Indonesia.go.id. Based on the analysis conducted, a total of 101 data of translation methods were found in the form of sentences, and 476 data of translation techniques in the form of words, phrases, clauses, and sentences. Of the 8 types of translation methods, 7 of them are found in this text including free translation, literal translation, communicative translation, semantic translation, adaptation, idiomatic translation, and word-for-word methods, and as many as 13 of 18 translation techniques are found including transposition techniques, literal, reduction translation technique, borrowing translation technique, established equivalent translation technique, calque technique, amplification, linguistic compression, discursive creation, modulation technique, linguistic amplification, adaptation, generalization. The most widely used translation method in this text is free translation, while transposition is the most widely used translation technique.